Monsoonal effect on sediment grain distribution along the subaqueous Mekong Delta coastal, Vietnam - Thanh N. C. Nguyen Cong (2024, 2024)
Annually, the coastal areas of the Mekong Delta receive approximately 50% of the total sediment load from the Mekong River, primarily during the southwest monsoon. During the northeast monsoon, this coastal sediment undergoes reworking and is transported southwestward along the coastal areas of the Mekong delta. Aim. Analyzing the grain-size distribution of sea-bed surface sediment helps improve our understanding of sediment redistribution along the coastal areas of the Mekong Delta. Methods. In order to illustrate changes in sea-bed surface sediment grain size between the two monsoons, we focused on the median grain size, a widely used parameter for sediment transport calculation, and created spatial maps of median grain size along the coastal areas of the Mekong Delta. The analysis was based on sediment samples collected along the coastal areas of the Mekong Delta during field excursions in the southwest and northeast seasons. Results. The results reveal that median grain size during northeast (mainly ranging from 0.005 to 0.01 mm) are larger than those during southwest (primarily ranging from 0.01 to 0.05 mm). These changes in median grain size and spatial distributions are most prominent along the east coast, specifically from Soc Trang to Bac Lieu. In contrast, median grain size along the west side does not exhibit significant differences between the southwest and northeast monsoons. These observations imply a more significant sediment transport along the east coastal areas of the Mekong Delta during the northeast monsoon and provide evidence for the transportation of sediment from the east coast to the west coast during the monsoons